2009
DOI: 10.1007/s11418-009-0368-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds from Cryptocarya konishii: their cytotoxic and tyrosine kinase inhibitory properties

Abstract: Two chalcone derivatives, 2'-hydroxychalcone (1) and desmethylinfectocaryone (2), together with five known phenolic compounds infectocaryone (3), cryptocaryone (4), kurzichalcolactone A (5), pinocembrin (6) and trans-N-feruloyltyramine (7), were isolated from the methanol extract of the wood of Cryptocarya konishii. The structures of the new compounds were determined based on the analysis of spectroscopic data, including UV, IR, 1D and 2D NMR, and mass spectra. Evaluation of the cytotoxic and tyrosine kinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 18 publications
(19 reference statements)
2
49
0
Order By: Relevance
“…15 This extract was found to be cytotoxic on HT-29 human colon cancer cells, as widely reported in the literature, where there are many evidences of the cytotoxicity of this dihydrochalcone on cancer cell lines, such as its ability to induce apoptosis through activation of caspases in prostate tumor. 16,17 Consistent with previous data, compound 2 showed an IC 50 value of 0.32 lM on HT-29 cells, and was found to cause a significant reduction of the uptake of glucose, implying that its anti-proliferative activity could be ascribed, at least in part, to GLUT inhibition.…”
Section: Introductionsupporting
confidence: 86%
“…15 This extract was found to be cytotoxic on HT-29 human colon cancer cells, as widely reported in the literature, where there are many evidences of the cytotoxicity of this dihydrochalcone on cancer cell lines, such as its ability to induce apoptosis through activation of caspases in prostate tumor. 16,17 Consistent with previous data, compound 2 showed an IC 50 value of 0.32 lM on HT-29 cells, and was found to cause a significant reduction of the uptake of glucose, implying that its anti-proliferative activity could be ascribed, at least in part, to GLUT inhibition.…”
Section: Introductionsupporting
confidence: 86%
“…Thus, compound 1 was identified as an analogue of kurzichalcolactone, a compound known to occur in Cryptocarya kurzii , 2 C. obovata , 4 and C. konishii . 6 Comparison of the 1 H- and 13 C NMR spectra of 1 with those of kurzichalcolactone 2 indicated that both compounds contain a comparable chalcone unit and a closely related side chain. In the 1 H- and 13 C NMR spectra of 1 , the signals due to a phenylethenyl group of kurzichalcolactone 2 were replaced by the signals assignable to a phenylethyl group.…”
Section: Resultsmentioning
confidence: 99%
“…6 This compound was reported to induce human prostate PC-3 cancer cell apoptosis through activation of caspases 3 and 8 8 and to inhibit NF-κB activation 5 and tyrosine kinase. 6 …”
mentioning
confidence: 99%
“…The genus Cryptocarya (Lauraceae) consists of about 250 species distributed mainly in the tropical and subtropical regions of the world. Earlier studies on this genus reported flavonoids [1][2][3][4][5][6][7][8], pyrones [6,[9][10][11][12], and alkaloids [13][14][15][16][17] as the main secondary metabolite constituents with varied biological activities. In our previous study, several flavonoids with a variety of bioactivities from C. maclurei and C. chingii were found [1,2].…”
mentioning
confidence: 99%
“…In our previous study, several flavonoids with a variety of bioactivities from C. maclurei and C. chingii were found [1,2]. As a part of our continuing search for bioactive constituents from tropical plants [1,2,[18][19][20], a 95 % EtOH extract of the stems of Cryptocarya concinna Hance with no previous literature reports on its chemistry has been investigated with five new (1)(2)(3)(4)(5) and six known flavonoids (6-11) obtained. Reported herein are the isolation, structure elucidation, and biological activities of these compounds.…”
mentioning
confidence: 99%